Autism awareness of mothers scale (AAMS): A study of validity and reliability - SARISALTIK, ALİCAN; HIDIROĞLU, SEYHAN; KARAVUŞ, MELDA (My University, 2023)
The aim of this study was to evaluate the autism awareness of mothers having typically developing children at preschool age and to investigate the validity and reliability of the Autism Awareness of Mothers Scale (AAMS). This methodological study was conducted with 136 mothers applying to a family health center in Istanbul, Türkiye. Data were collected in July-August 2021. The AAMS was a 4-point Likert-type scale and consisted of a total of 23 items. The factor structure of the scale was extracted by performing exploratory factor analysis. The median age of the participants was 32 years. Almost all the participants (91.9%) stated that they had heard the word ‘autism’ before. One-third of the mothers defined autism as a “social interaction problem” (33.1%). As a result of factor analysis, the AAMS had a two-factor structure, with Eigenvalues of 7.480 for Factor 1 and 4.978 for Factor 2 and explained 54.17% of total variance. The Cronbach's alpha coefficient was found to be 0.947 for AAMS (0.933 and 0.876 for subscales, respectively). According to our results, AAMS is a valid and reliable measurement tool. It can be used in Türkiye and in Turkish to determine autism awareness of mothers of typically developing preschool children.

Bu çalışmanın amacı, okul öncesi dönemde ve normal gelişim gösteren çocuğu olan annelerin otizm farkındalıklarını değerlendirmek ve Annelerin Otizm Farkındalık Ölçeği'nin (AOFÖ) geçerlik ve güvenirliğini araştırmaktır. Bu metodolojik araştırma, İstanbul ilinde bir aile sağlığı merkezine başvuran 136 anne ile yapıldı. Veriler Temmuz-Ağustos 2021 tarihlerinde toplandı. AOFÖ 4'lü Likert tipinde bir ölçek olup toplam 23 maddeden oluşmaktaydı. Açımlayıcı faktör analizi yapılarak ölçeğin faktör yapısı çıkarıldı. Katılımcıların ortanca yaşı 32 idi ve tamamına yakını (%91,9) 'otizm' kelimesini daha önce duyduklarını belirttiler. Annelerin üçte biri otizmi “sosyal etkileşim sorunu” olarak tanımladı (%33,1). Faktör analizi sonucunda AOFÖ’nün özdeğerleri sırasıyla 7.480 ve 4.978 olan iki faktörlü bir yapıya sahip olduğu ve toplam varyansın %54,17'sini açıkladığı görüldü. AOFÖ için Cronbach alfa katsayısı 0,947 olarak bulundu (alt ölçekler için sırasıyla 0,933 ve 0,876). Sonuçlarımıza göre AOFÖ geçerli ve güvenilir bir ölçme aracıdır. Okul öncesi dönemde çocukları olan annelerin otizm farkındalıklarını belirlemek için Türkiye'de ve Türkçe olarak kullanılabilir.
Annelerin otizm farkındalığı ölçeği (AOFÖ): Geçerlik ve güvenirlik çalışması
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Otizm; farkındalık; anne; okul öncesi; ölçek; Autism; awareness; mother; preschooler; scale.